2013
DOI: 10.1128/aac.02264-12
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Characterization of an rsmD -Like rRNA Methyltransferase from the Wolbachia Endosymbiont of Brugia malayi and Antifilarial Activity of Specific Inhibitors of the Enzyme

Abstract: bThe endosymbiotic organism Wolbachia is an attractive antifilarial drug target. Here we report on the cloning and expression of an rsmD-like rRNA methyltransferase from the Wolbachia endosymbiont of Brugia malayi, its molecular properties, and assays for specific inhibitors. The gene was found to be expressed in all the major life stages of B. malayi. The purified enzyme expressed in Escherichia coli was found to be in monomer form in its native state. The activities of the specific inhibitors (heteroaryl com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 60 publications
0
5
0
Order By: Relevance
“…Accordingly, homologous proteins of E. coli RsmD are present in higher plant chloroplasts ( Supplementary Figures 3 , 4 ) but are completely absent in both Archaea and Eukarya. The AtRsmD protein shares highly conserved motifs, such as Dx(F/G/Y)xGxG and (D/N/T)PP(F/Y), with those in E. coli ; these motifs are required for S-adenosyl-L-methionine (SAM) binding ( Supplementary Figure 3 ; Rana et al, 2013 ; Ngoc et al, 2021b ). Importantly, a recent report demonstrated that AtRsmD is a MTase responsible for chloroplast 16S rRNA m 2 G 915 methylation, which is absent in the atrsmd-1 mutant ( Ngoc et al, 2021b ).…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, homologous proteins of E. coli RsmD are present in higher plant chloroplasts ( Supplementary Figures 3 , 4 ) but are completely absent in both Archaea and Eukarya. The AtRsmD protein shares highly conserved motifs, such as Dx(F/G/Y)xGxG and (D/N/T)PP(F/Y), with those in E. coli ; these motifs are required for S-adenosyl-L-methionine (SAM) binding ( Supplementary Figure 3 ; Rana et al, 2013 ; Ngoc et al, 2021b ). Importantly, a recent report demonstrated that AtRsmD is a MTase responsible for chloroplast 16S rRNA m 2 G 915 methylation, which is absent in the atrsmd-1 mutant ( Ngoc et al, 2021b ).…”
Section: Discussionmentioning
confidence: 99%
“…The mosquitoes were fed on infected donor animals. On day 9 ± 1, infective larvae (L3) of B. malayi were recovered from fed mosquitoes by the Baermann method [15]. …”
Section: Methodsmentioning
confidence: 99%
“…, 132 (30), and 104 (37). (CAS # 488746-10-7] [40] Solid; yield: 80%; M.P: 294-296°C; [43] Solid; yield: 85%; M.P: 278-282°C;…”
Section: General Procedures For the Synthesis Of Compounds 4-30mentioning
confidence: 99%
“…The synthetic library of isatin thiazole derivatives was evaluated for their α‐amylase and α‐glucosidase inhibitory activities and all compounds showed good to moderate results. The series consists of three intermediates ( 3a–c ) which are reported in the literature, [ 38–40 ] among the 27 derivatives ( 4–30 ), 15 compounds 5, 8, 9, 11–13, 18, 20, 21, 23, 24, 26, 27, 29 , and 30 are new; while 12 compounds 4, 6, 7, 10, 14–17, 19, 22, 25 , and 28 were previously reported in the literature [ 41–47 ] (Figure ).…”
Section: Introductionmentioning
confidence: 97%